Claimed medical malpractice in fatal SARS-CoV-2 infections: the importance of combining ante- and post-mortem radiological data and autopsy findings for correct forensic analysis. (June 2021) - Filograna, Laura; Manenti, Guglielmo; Arena, Vincenzo; Dell'Aquila, Marco; Pascali, Vincenzo L.; Natale, Luigi; Colosimo, Cesare; Grassi, Simone; Floris, Roberto; Oliva, Antonio
Highlights: During SARS-CoV-2 pandemic, issues regarding the legal liability of healthcare professionals for avoidable errors arouse. PMCT can be used for post-mortem investigation in patients infected with SARS-CoV-2. Improving the knowledge of ante- and post-mortem imaging and autopsy pathology is crucial for finding the cause of the death in SARS-CoV-2 patients. In the first wave, the legal responsibility of the healthcare professionals was limited only to cases of gross negligence Abstract: We present the case of an elderly woman who died from COVID-19 during the first wave of the pandemic. The physicians in charge of the patient were later accused of medical malpractice resulting in the death of the patient. The article reviews the comprehensive medico-legal investigations into this case that included an analysis of the medical history, clinical imaging, post-mortem imaging, autopsy, histopathology, and microbiology as well as an assessment of the medical knowledge regarding transmission of the SARS-CoV-2 virus and the management of COVID-19 at the time of the patient's death. The investigation resulted in a verdict of not guilty. This case highlights the value of clinical and post-mortem imaging as well as various challenges of medico-legal investigations of COVID-19 related deaths.